2020
DOI: 10.1177/0969141320953206
|View full text |Cite
|
Sign up to set email alerts
|

Time of day and mammographic reader performance in a population-based breast cancer screening programme

Abstract: Objectives To analyse how reader performance varied by time during the day in a population-based breast cancer screening programme. Methods A total of 2,937,312 readings from 148 radiologists and 1,468,656 women were included in this study from Norway. Number and percentages of mammographic readings, positive scores, true and false positive readings, true and false negative readings, sensitivity and specificity were presented for categories of time of day and for each day of the week. Multilevel mixed effect l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, screen reading hundreds of mammograms might cause fatigue, and it is expected that a decrement in vigilance will affect the performance. A recent study demonstrated a decrease in sensitivity and increase in specificity for breast radiologists throughout the day [7]. Based on these findings, we expect a decline in sensitivity throughout a batch of screen readings.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, screen reading hundreds of mammograms might cause fatigue, and it is expected that a decrement in vigilance will affect the performance. A recent study demonstrated a decrease in sensitivity and increase in specificity for breast radiologists throughout the day [7]. Based on these findings, we expect a decline in sensitivity throughout a batch of screen readings.…”
Section: Introductionsupporting
confidence: 54%
“…Menopausal status, use of hormonal treatment, and mammographic density are examples of risk factors [2][3][4][5], while screening interval, age range of the target population, and availability to prior mammograms are examples of organizational factors [6]. The radiologists' experience, time of day, reading volume each day, time spent reading, number of reading sequences (batches), and size of the batches are examples of factors expected to be of influence for the radiologists' performance [6][7][8][9][10][11]. However, the evidence concerning the relative importance of these factors is sparse and the studies are often performed in a test or educational setting.…”
Section: Introductionmentioning
confidence: 99%
“…In a study from BreastScreen Norway, an annual screening volume between 4000-10 000 screen-readings was considered to give the most optimal screening performance (141). In addition, time and length of the screen-reading session may impact radiologists' performance by influencing attention and vigilance (145).…”
Section: Challenges In Mammographic Screeningmentioning
confidence: 99%
“…2,3 Some of these properties depend on viewing history and can include long-term factors, such as perceptual learning and visual expertise, 4,5 as well as short-term changes from sequential reading effects, particularly when images are read in batches as in breast-cancer screening exams. A number of sequential effects such as fatigue, 6,7 vigilance, 8 and sequential bias 9 have been examined as potential sources of degraded reading performance. In this work, we investigate sequential effects resulting from visual adaptation, or changes in visual sensitivity that result from changes in the stimulus.…”
Section: Introductionmentioning
confidence: 99%